2013
DOI: 10.1021/ma400454u
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Controlled Radical Polymerization of N-Substituted Maleimides with 1-Methylenebenzocycloalkanes and the Characterization of the Obtained Copolymers with Excellent Thermal Resistance and Transparency

Abstract: The radical copolymerization of N-methyl, ethyl, n-butyl, and 2-ethylhexylmaleimides (RMIs) with 1-methylenebenzocycloalkanes (BCms) was carried out to fabricate thermally stable and transparent polymer materials. The copolymerization reactivity of BCms significantly depended on the carbon number of the ring structure of BCms. The analyses of the comonomer–copolymer composition curves and theoretical calculations results revealed that the sequence-controlled copolymerization of RMIs with BCms occurred in alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 66 publications
3
39
0
Order By: Relevance
“…Recent years, transparent polymers with a high T g and excellent properties are one of the key materials for electronic and photonic applications, and therefore, various types of polymers and their composites have been developed as highperformance transparent materials. [16,[28][29][30][31] It is noted that the radical copolymerization of the RMIs and the postpolymerization using thiol/ene reactions are useful as the method for high-performance polymer materials production. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years, transparent polymers with a high T g and excellent properties are one of the key materials for electronic and photonic applications, and therefore, various types of polymers and their composites have been developed as highperformance transparent materials. [16,[28][29][30][31] It is noted that the radical copolymerization of the RMIs and the postpolymerization using thiol/ene reactions are useful as the method for high-performance polymer materials production. …”
Section: Resultsmentioning
confidence: 99%
“…[12,13] The introduction of polar groups and cyclic structures into the olefin repeating units led to further increases in their thermally stability and the T g values. [14][15][16] Recently, we demonstrated that the copolymerization of the RMIs provided copolymers with finely controlled structures in the 1:1 alternating and 2:1 sequence-controlled fashions, depending on the steric bulkiness and conjugated structure of olefin and styrene derivatives. [17,18] The sophisticated AAB-type sequence structures were produced during the copolymerization under penultimate unit control (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The BC5 and BC6 had a planar molecular structure, while BC7 showed a strained and nonplanar structure. 39 The production of the copolymers with a 2:1 composition by deviation from the planar structure of the monomer is considered to be related to a decrease in the monomer reactivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, the ratedetermining step is the addition of an olefin monomer to an RMI propagating radical during the copolymerization of RMI with an olefin. 39 Both cross-propagations can be accelerated by the introduction of an electron-donating substituent into the olefin structure. The copolymerization results in Table 4 were tried to analyze using the Taft's steric and the Hammett's polar substituent constants.…”
Section: Macromoleculesmentioning
confidence: 99%
“…Matsumoto et al [54] and Kamigaito et al [16,55] independently reported that maleimides showed unique 2:1 co-polymerization behaviors with D-limonene or 1-methylenebenzocycloalkanes. Using functionalized limonene or maleimide derivatives as monomer pairs, periodical copolymers with functional moieties, such as hydroxyl and chlorine, in ABB triad sequence were obtained.…”
Section: Chain Growth Polymerization 41 Alternating (Co)polymermentioning
confidence: 99%